Effect of prior vaccination on carriage rates of Streptococcus pneumoniae in older adults: A longitudinal surveillance study - Branche, Angela R.; Yang, Hongmei; Java, James; Holden-Wiltse, Jeanne; Topham, David J.; Peasley, Michael; Frost, Michael R.; Nahm, Moon H.; Falsey, Ann R. (Vaccine, 2018)
Pneumococcus is a commensal of the upper respiratory tract and colonization is common in young children. Carriage studies have provided insights on vaccine effects in children and may also be useful for assessing vaccines in adults. However, culture based prevalence studies in older adults describe low colonization rates. Therefore, we assessed cumulative incidence of pneumococcal colonization in older adults using polymerase chain reaction (PCR) targeting the lytA gene and risk factors for carriage. 100 community-dwelling adults ≥65 years were enrolled the winter of 2015 and followed biweekly for 12 months. Medical, vaccination and illness history as well as nasopharyngeal (NP) and oropharyngeal (OP) samples were collected. Combined OP and NP were incubated in enrichment broth and screened using real-time lytA PCR. Samples from new colonization events (lytA PCR+) were cultured on gentamicin blood agar plates. Isolates identified by colony morphology as S. pneumoniae were serotyped using a multiplex combined immunoassay-PCR platform which classifies 96 serotypes. Cumulative incidence of pneumococcal carriage was calculated and risk factors for carriage assessed. The cumulative incidence of colonization was 41% by PCR and 14% by culture. Monthly prevalence ranged from 0 to 17% by PCR and 1 to 4% by culture with peaks in the spring and fall. Demographics were similar between colonized and never colonized subjects although colonized were younger (72.4 vs. 75.0 years, P = 0.06). Vaccination with any pneumococcal vaccine before or during study period was associated with decreased risk of becoming colonized (p < 0.001) as was vaccination with either the 13-valent conjugated pneumococcal vaccine (PCV13) or 23-valent polysaccharide vaccine (PPSV23) (p < 0.001). Pneumococcal colonization in older adults as detected by lytA PCR is frequent and pneumococcal vaccination appears to be associated with decreased risk of carriage. Further study is needed to understand the biological significance of molecular detection of pneumococcus in adults.